Structural requirement of isoflavonones for the inhibitory activity of interleukin-5 - Jung, SH; Cho, SH; Dang, TH; Lee, JH; Ju, JH; Kim, MK; Lee, SH; Ryu, JC; Kim, Y (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2003)
Sophoricoside isolated from Sophora japonica is a glycoside of isoflavonone as an inhibitor of interleukin (IL)-5. To identify structural requirements of this isoflavonone for its inhibitory activity against IL-5, isoflavonones, isoflavanones, and their glycosides were prepared and their inhibitory activity was tested against IL-5. Among them, 5-benzyloxy-3-(4-hydroxyphenyl)chromen-4-one (4b, 87.9% inhibition at 50 muM, IC50 = 15.3 muM) shows the most potent activity, comparable with that of sophoricoside. The important structural requirements of these isoflavonone analogs exhibiting the inhibitory activity against IL-5 were recognized as (1) planarity of chromen-4-one ring, (2) existence of phenolic hydroxyl at 4-position of B ring, and (3) introduction of benzyloxy at 5-position, which may act as a bulky group for occupying hydrophobic pocket in putative binding site. However the glucopyranosyl moiety of sophoricoside is not an essential motif for the activity. (C) 2003 Editions scientifiques et medicales Elsevier SAS. All rights reserved.
Keywords: AIRWAY HYPERRESPONSIVENESS; SOPHORICOSIDE ANALOGS; MOLECULAR-CLONING; IL-5; EOSINOPHILIA; EXPRESSION; HYPERREACTIVITY; RECEPTORS; BINDING; LEADS